The in vivo respiratory phenotype of the adenosine A1 receptor knockout mouse - Heitzmann, Dirk (Respiratory physiology & neurobiology, 2016)
The nucleoside adenosine has been implicated in the regulation of respiration, especially during hypoxia in the newborn. In this study the role of adenosine A1 receptors for the control of respiration was investigated in vivo. To this end, respiration of unrestrained adult and neonatal adenosine A1 receptor knockout mice (A1R-/- ) was measured in a plethysmographic device. Under control conditions (21% O2) and mild hypoxia (12-15% O2) no difference of respiratory parameters was observed between adult wildtype (A1R+/+) and A1R-/- mice. Under more severe hypoxia (6-10% O2) A1R+/+ mice showed, after a transient increase of respiration, a decrease of respiration frequency (fR) and tidal volume (VT) leading to a decrease of minute volume (MV). This depression of respiration during severe hypoxia was absent in A1R-/- mice which displayed a stimulated respiration as indicated by the enhancement of MV by some 50-60%. During hypercapnia-hyperoxia (3-10% CO2/97-90 % O2), no obvious differences in respiration of A1R-/- and A1R+/+ was observed. In neonatal mice, the respiratory response to hypoxia was surprisingly similar in both genotypes. However, neonatal A1R-/- mice appeared to have more frequently periods of apnea during hypoxia and in the post-hypoxic control period. In conclusion, these data indicate that the adenosine A1 receptor is an important molecular component mediating hypoxic depression in adult mice and it appears to stabilize respiration of neonatal mice.